2021
DOI: 10.3390/jmse9060618
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pile Diameter and Aspect Ratio on the Lateral Response of Monopiles in Sand with Different Relative Densities

Abstract: The large-diameter monopiles are the most preferred foundation used in offshore wind farms. However, the influence of pile diameter and aspect ratio on the lateral bearing behavior of monopiles in sand with different relative densities has not been systematically studied. This study presents a series of well-calibrated finite-element (FE) analyses using an advanced state dependent constitutive model. The FE model was first validated against the centrifuge tests on the large-diameter monopiles. Parametric studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Considering that the soil failure modes of fixed-head flexible pile are similar to that of the free head (i.e., wedge failure at shallow and flow around at deep zone), no further simulation was performed under this condition. The pile configurations were selected to cover the applications in existing and future offshore wind projects, i.e., D > 6 m and L/D < 8 (Negro et al 2017;Wang et al 2021a, b). The loading eccentricity is 5 m in all cases, since existing studies show that pile-soil interaction is not affected by the loading eccentricity (Klinkvort 2013;Wang et al 2022).…”
Section: Analytical and Numericalmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the soil failure modes of fixed-head flexible pile are similar to that of the free head (i.e., wedge failure at shallow and flow around at deep zone), no further simulation was performed under this condition. The pile configurations were selected to cover the applications in existing and future offshore wind projects, i.e., D > 6 m and L/D < 8 (Negro et al 2017;Wang et al 2021a, b). The loading eccentricity is 5 m in all cases, since existing studies show that pile-soil interaction is not affected by the loading eccentricity (Klinkvort 2013;Wang et al 2022).…”
Section: Analytical and Numericalmentioning
confidence: 99%
“…The constitutive model has been implemented in Abaqus by the user-defined subroutine (Gudehus et al 2008) and used in different applications (e.g., Ng et al 2013). In this study, the model parameters (summarized in Table 3) for Toyoura sand were adopted, which have been calibrated against element test (Hong et al 2016) and validated against centrifuge pile test in medium dense sand (D r = 65%) (Wang et al 2021a(Wang et al , 2021b(Wang et al , 2022. Details about the sand, model calibration, and validation can be found in Ishihara (1993)…”
Section: Analytical and Numericalmentioning
confidence: 99%
“…The steel winged monopiles are assumed to be linearly elastic with Young's modulus E p = 210 GPa and Poisson's ratio ν p = 0.3, similar to previous studies on pile foundations [27][28][29]. The Young's modulus of sand E s for describing the elastic behavior is stress-dependent and increases with the earth pressure at rest [30]:…”
Section: Constitutive Modelmentioning
confidence: 99%
“…The "hard contact" model allows separation in the normal direction, while the Coulomb friction model is adopted in the tangential direction. The interface friction angle δ is taken as 2/3ϕ 0 to simulate the typical steel-sand contact property [29,42], where ϕ 0 is the constant friction angle. The value of ϕ 0 can be estimated according to the formula recommended by API [43]:…”
Section: Constitutive Modelmentioning
confidence: 99%
“…By using the finite-element method, incorporating a state-dependent constitutive model of sand, the influence of pile diameter and aspect ratio on the lateral response of monopiles was numerically investigated [3]. It was revealed that the rotation failure mechanism of a rigid pile is independent of pile diameter and aspect ratio.…”
Section: (1) Pile or Monopile Foundationsmentioning
confidence: 99%